Generalized diffusion theory of non-rotational, rigid spherical particle sedimentation in viscous fluid - Phan, Nguyen Hong; Diep, Nguyen Van (Vietnam Journal of Mechanics, 2001)
This paper is devoted to application of Generalized Diffusion Theory for solving a sedimentation problem of rigid spherical particles in viscous fluid. The governing equations have been obtained. It is shown that, in this case the governing equation system is a hyperbolic one, and the equations in the characteristic form have been derived. The mathematical properties of the obtained equation system and the solution for stationary sedimentation where investigated numerically